The Study of Discourse on Digital Pathology and Spiritual Education - Subhan Fadli; Zain Sartono (Eduvest - Journal of Universal Studies, 2023)
Pathological behavior is any form of behavior considered by most citizens of society as  disturbing,  undesirable,  harmful,  and  detrimental  to  public  because  it  violates community customs (and these customs are necessary to ensure the prosperity of  living together). Digital pathology is different from the disciplines of Islamic morality or moral science. If it is moral science, it is a discipline that discusses the ideal form of Muslim personality and strives so that this ideal can be applied in the real life of a Muslim, while digital pathology is a discipline that focuses on examining the non-ideal/negative form of child/adolescent personality and seeks to overcome it. This study  aims  to  present  a  discourse  on  digital  pathology  and  spiritual  education discourse  to  obtain  a  definitive  formulation  of  digital  pathology  and  spiritual education  and  affirm  the  concept  of  spiritual  education  that  is  relevant to this researcher.  This  study,  begins by expressing  anthropocentric,  sociological, and theocentric   views   on   spiritual   education   and   digital  pathology and their dimensional dimensions. This study uses a qualitative method. Qualitative research is  an umbrella  concept  that  includes  several  research  formats  that  will  help understand  and  explain  the  meaning  of  social  phenomena  from  existing  natural settings. Overcoming digital pathology through Qur'an-based spiritual education is a conscious effort in overcoming and preventing diseases caused by devices, namely various social and individual crises that include identity crises, legality, penetration, participation,  distribution  and  moral  crises.